The Magnitude and Distribution of Fuel Subsidies : Evidence from Bolivia, Ghana, Jordan, Mali, and Sri Lanka - Gillingham, Robert (IMF Working Papers; Working Paper ;, 2006)
With the recent jump in world oil prices, the issue of petroleum product pricing has become increasingly important in developing countries. Reflecting a reluctance of many governments to pass these price increases onto energy users, energy price subsidies are absorbing an increasing share of scarce public resources. This paper identifies the issues that need to be discussed when analyzing the fiscal and social costs of fuel subsidies. Using examples from analyses recently undertaken for five countries, it also identifies the magnitude of consumer subsidies and their fiscal implications. The results of the analysis show that-in all of these countries-energy subsidies have significant social and fiscal costs and are badly targeted.